Occurrence of Chlamydia trachomatis infection in pregnant women with preterm complications and stillbirths - Sulaiman, Nurshahira (2012)
This study aims to determine the occurrence of C. trachomatis infection across a multi-ethnic cohort of pregnant women who presented with preterm complications and stillbirths and to determine the risk factors for C. trachomatis infection. This study also detects C. trachomatis using nested PCR and PCR ELISA as the screening tools. A cross-sectional study on pregnant women less than 37 weeks of pregnancy who presented with preterm contractions, preterm premature rupture of membranes and stillbirths was carried out in two public hospitals in Southern Selangor, Malaysia. A total of 106 endocervical swabs obtained were subjected to DNA amplification using Nested PCR (BioSewoom, Korea) and PCR-ELISA (Roche, USA) for C. trachomatis detection.Self-administered questionnaires were used to collect data on demographic and behavioural factors. In addition, C. trachomatis was detected in 43% of women with preterm complications and in 62% of women with stillbirths. Multiple logistic regression analysis indicated that mothers who were less than 25 years old of age (OR 2.731; 95% CI: 1.139, 6.549) and Chinese ethnicity (OR 17.799; 95% CI: 1.406, 225.387) were significant independent risk factors for chlamydial infection (p<0.05). High prevalence of C. trachomatis infection was observed among women with preterm complications and stillbirths. This study supports the essential need to screen pregnant women with preterm complications and stillbirths for infection with C. trachomatis using highly sensitive PCR ELISA. Thus, early intervention such as antibiotic therapy can be instituted at the earliest possible time with appropriate screening guidelines to reduce the adverse outcomes of C. trachomatis infection.